2021
DOI: 10.3390/children8020129
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Student’s Mental Health: A Cross-Sectional Survey for School Nurses

Abstract: Children’s and adolescents’ health problems are often related to mental health, and their wellbeing should be supported in schools. This study describes school nurses’ role and how equipped they are in recognizing students’ mental health needs and in supporting students’ mental health. Moreover, we explored the methods used and the barriers that exist for supporting students’ mental health. A national survey for members of the Finnish Public Health Association working as school nurses was conducted (n = 136/64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Participants perceived the training as filling the gaps in their earlier education. Previous studies have already suggested that the degree training for school nurses does not provide sufficient expertise in mental health issues (Markkanen et al, 2021;Putkuri et al, 2021;Putkuri et al, 2023), and our results strengthen these findings. Participants in our study were satisfied with the clear and concise structure and content as well as with inspiring and interesting design.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Participants perceived the training as filling the gaps in their earlier education. Previous studies have already suggested that the degree training for school nurses does not provide sufficient expertise in mental health issues (Markkanen et al, 2021;Putkuri et al, 2021;Putkuri et al, 2023), and our results strengthen these findings. Participants in our study were satisfied with the clear and concise structure and content as well as with inspiring and interesting design.…”
Section: Discussionsupporting
confidence: 83%
“…School nurses' competence in mental health issues has proved to be insufficient (Markkanen et al, 2021) and they need evidence-based education on managing mental health issues (Putkuri et al, 2021;Kaskoun and McCabe, 2022). In our earlier study, we identified those topics needed in continuing education, such as assessment tools, etiology and symptoms of mental disorders, the chain of care paths, preventive interventions, methods of psychosocial treatment and medical treatment (Putkuri et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research identified that therapeutic engagement, the development of trust, health counselling and interprofessional collaboration were key activities school nurses undertook with individual students (Dina & Pajalic, 2014). Similarly, Markkanen et al (2021) identified that individual counselling, crisis intervention and assessment of emotional or behavioural problems were frequent school nurse activities. Participants in the current study described undertaking similar tasks, but these were conceptualized in goal-directed terms and oriented to optimizing outcomes in the young person's life.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the experiences of secondary school nurses with young people experiencing mental health problems (Dina & Pajalic, 2014;Hilli & Wasshede, 2017;Jönsson et al, 2017;Pryjmachuk et al, 2012;Skundberg-Kletthagen & Moen, 2017). A common finding is that school nurses perceive their work with this cohort to be an important part of their role (Markkanen et al, 2021;Pryjmachuk et al, 2012;Skundberg-Kletthagen & Moen, 2017), but they do not always feel well-equipped clinically or professionally for the work (Jönsson et al, 2017;Markkanen et al, 2021;Moen & Skundberg-Kletthagen, 2018;Skundberg-Kletthagen & Moen, 2017). Several studies have identified that school nurses experience unease caring for this cohort (Jönsson et al, 2017;Markkanen et al, 2021;Pryjmachuk et al, 2012;Skundberg-Kletthagen & Moen, 2017;Thomas, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation